1999
DOI: 10.1021/jp983432t
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Orientation of Benzophenone Crystals in Fields up to 80.0 KOe

Abstract: The magnetic orientation of benzophenone crystals (diamagnetism) has been studied in various intensities of fields (0.0-80.0 kOe). As the field intensity is increased, the proportion of oriented crystals increases. The orientation is found to follow the Boltzmann distribution for crystals possessing different magnetic energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…(1) [8] EðN;q;HÞ ZK 1 2 where m 0 is the magnetic permeability of vacuum, n is the mole number of the crystal, c i is the molar magnetic susceptibility along the i axis, q is the angle between the c 1 and the magnetic field direction, and H is the magnetic field strength. In Eq.…”
Section: Magnetic Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) [8] EðN;q;HÞ ZK 1 2 where m 0 is the magnetic permeability of vacuum, n is the mole number of the crystal, c i is the molar magnetic susceptibility along the i axis, q is the angle between the c 1 and the magnetic field direction, and H is the magnetic field strength. In Eq.…”
Section: Magnetic Orientationmentioning
confidence: 99%
“…Orientation of inorganic and organic aggregates is very important technique for improving the quality of materials in material chemistry. Our group has studied magnetic orientation of organic crystals [8] and carbon nanotubes [9]. By using quasi-microgravity generated by magnetic force, X-ray crystallographic quality of lysozyme crystals is improved [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the anisotropy of the susceptibility is very large, a magnetic orientation effect is expected when the crystal grows in magnetic fields. In the case of crystal growth from the solution in magnetic fields, it has been reported that the crystals grew as the c-axis is perpendicular to the magnetic field [12].…”
Section: Containerless Crystallization Of Benzophenonementioning
confidence: 99%
“…Here the interesting question arises up to which size the crystals can reorient in the field before they settle to the bottom of the vessel. Recently, Fujiwara et al 46 reported a study of the magnetic field dependence of the order parameter of benzophenone crystals grown in a magnetic field. Here crystal needles of about 1 cm length were formed and the order parameter was determined by visually evaluating the statistics of crystal orientations.…”
Section: Macroscopic Forcesmentioning
confidence: 99%